Ramadan excursion to Palu evokes sense of humility - UMP, PNC (2019)
An excursion during the recent fasting month of Ramadan to the district of Palu in the centre of Sulawesi, Indonesia, evoked a sense of humility among volunteers from Universiti Malaysia Pahang (UMP), who personally experienced self-effacement when they extended a helping hand to the victims of last September’s double catastrophe of earthquake and tsunami.